Improved Outcomes following the Establishment of a Neurocritical Care Unit in Saudi Arabia - Ibrahim Soliman; Waleed Tharwat Aletreby; Fahad Faqihi; Nasir Nasim Mahmood; Omar E. Ramadan; Ahmad Fouad Mady; Babar Kahlon; Abdulrahman Alharthy; Peter Brindley; Dimitrios Karakitsos (Critical Care Research and Practice)
Background. Dedicated neurocritical care units have dramatically improved the management and outcome following brain injury worldwide. Aim. This is the first study in the Middle East to evaluate the clinical impact of a neurocritical care unit (NCCU) launched within the diverse clinical setting of a polyvalent intensive care unit (ICU). Design and Methods. A retrospective before and after cohort study comparing the outcomes of neurologically injured patients. Group one met criteria for NCCU admission but were admitted to the general ICU as the NCCU was not yet operational (group 1). Group two were subsequently admitted thereafter to the NCCU once it had opened (group 2). The primary outcome was all-cause ICU and hospital mortality. Secondary outcomes were ICU length of stay (LOS), predictors of ICU and hospital discharge, ICU discharge Glasgow Coma Scale (GCS), frequency of tracheostomies, ICP monitoring, and operative interventions. Results. Admission to NCCU was a significant predictor of increased hospital discharge with an odds ratio of 2.3 (95% CI: 1.3–4.1; p=0.005). Group 2 (n = 208 patients) compared to Group 1 (n = 364 patients) had a significantly lower ICU LOS (15 versus 21.4 days). Group 2 also had lower ICU and hospital mortality rates (5.3% versus 10.2% and 9.1% versus 19.5%, respectively; all p<0.05). Group 2 patients had higher discharge GCS and underwent fewer tracheostomies but more interventional procedures (all p<0.05). Conclusion. Admission to NCCU, within a polyvalent Middle Eastern ICU, was associated with significantly decreased mortality and increased hospital discharge.